1993
DOI: 10.1007/bf00000714
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short-term acute cadmium exposure on blue tilapia,Oreochromis aureus

Abstract: SynopsisDisease-free blue tilapia, Oreochromis aureus, exposed to cadmium (OSppm and 10ppm) showed very significant and dramatic decrease in food consumptions. Food consumptions returned to near normal 21 days after fish were returned to cadmium-free water. Along with anorexia there were decreases in body weights during the period when fish were exposed to cadmium. Fish in cadmium-free water that were pair-fed to cadmium-exposed fish (0.5 ppm) did not gain weight but there were no decreases in body weights. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Growth parameters were calculated as follows: specific growth rate (SGR)=100×[{1n(end mass)−ln(start mass)}/time]; liver somatic index (LSI)=(liver weight/body ed by several factors, including time, temperature, interacting agents, fish age, fish metabolic activity, and the biological halflife of the metal (Larsson et al, 1985;Douben, 1989;Woo et al, 1993;Heath, 1995;Kargin, 1996;Nielsen and Andersen, 1996). Metal elimination studies are important in terms of fish health, as they help to determine the self-cleansing ability of contaminated organisms and to assess the biological half-life for various metallic contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…Growth parameters were calculated as follows: specific growth rate (SGR)=100×[{1n(end mass)−ln(start mass)}/time]; liver somatic index (LSI)=(liver weight/body ed by several factors, including time, temperature, interacting agents, fish age, fish metabolic activity, and the biological halflife of the metal (Larsson et al, 1985;Douben, 1989;Woo et al, 1993;Heath, 1995;Kargin, 1996;Nielsen and Andersen, 1996). Metal elimination studies are important in terms of fish health, as they help to determine the self-cleansing ability of contaminated organisms and to assess the biological half-life for various metallic contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney is the organ most sensitive to the toxic e!ects of cadmium (Woo et al, 1993). Excessive exposure to cadmium will produce consistent proteinuria, and proteinuria appears to be the most sensitive indication of the renal toxicity (Nicholson et al, 1983).…”
Section: Introductionmentioning
confidence: 97%
“…Published literature on the effect of Cd on fish feeding is rare. Woo et al (1993) showed that the short-term effect of Cd is reduced pelleted food intake in blue tilapia, Oreochromis aureus.…”
Section: Discussionmentioning
confidence: 99%